The Association between Visionary Leadership and Teachers’ Achievement Motivation: The Mediating Role of Work-Life Balance - Huri Suhendri; Mailizar Mailizar; Rita Ningsih (FOUNDAE (Foundation of Advanced Education), 2026)
Teachers’ achievement motivation is a critical factor influencing educational quality and teacher performance. Although previous studies have examined leadership, teacher motivation, and work-life balance independently, limited research has explored the mechanism through which visionary leadership influences teachers’ achievement motivation, particularly within vocational education settings. This study investigates the association between visionary leadership and teachers’ achievement motivation, with work-life balance as a mediating variable among private vocational school teachers in Indonesia. A quantitative cross-sectional survey was conducted involving 127 mathematics teachers selected through proportionate stratified random sampling. Data were collected using Likert-scale questionnaires and analyzed using multiple regression and path analysis. The results revealed that visionary leadership was positively associated with teachers’ achievement motivation (β = 0.553, p < .001) and work-life balance (β = 0.496, p < .001). Work-life balance was also positively associated with achievement motivation (β = 0.618, p < .001). Furthermore, the findings indicated that work-life balance mediated the relationship between visionary leadership and teachers’ achievement motivation. These findings suggest that visionary leadership is associated not only with higher teacher motivation but also with more balanced professional and personal lives among teachers. The study contributes to educational management literature by integrating leadership and well-being perspectives into a unified framework for explaining teacher motivation and highlights the importance of supporting teachers’ work-life balance to foster achievement motivation in vocational education contexts.